Material encounters and indigenous transformations in the early colonial Americas : archaeological case studies - Hofman, Corinne L., 1959-; Keehnen, Floris W. M. (Early Americas: history and culture, 2019)
"Material Encounters and Indigenous Transformations in the Early Colonial Americas brings together 15 case studies focusing on the early colonial history and archaeology of indigenous cultural persistence and change in the Caribbean and its surrounding mainland(s) after AD 1492. With a special emphasis on material culture and by foregrounding indigenous agency in shaping the diverse outcomes of colonial encounters, this volume offers new perspectives on early modern cultural interactions in the first regions of the 'New World' that were impacted by European colonization. The volume contributors specifically investigate how foreign goods were differentially employed, adopted, and valued across time, space, and scale, and what implications such material encounters had for indigenous social, political, and economic structures Contributors are: Andrzej T. Antczak, Ma. M. Antczak, Oliver Antczak, Jaime J. Awe, Martijn van den Bel, Mary Jane Berman, Arie Boomert, Jeb J. Card, Charles R. Cobb, Gérard Collomb, Shannon Dugan Iverson, Marlieke Ernst, William R. Fowler, Perry L. Gnivecki, Christophe Helmke, Shea Henry, Gilda Hernández Sánchez, Corinne L. Hofman, Menno L.P. Hoogland, Rosemary A. Joyce, Floris W.M. Keehnen, J. Angus Martin, Clay Mathers, Maxine Oland, Alberto Sarcina, Russell N. Sheptak, Roberto Valcárcel Rojas, Robyn Woodward"--